2022
DOI: 10.4046/trd.2022.0053
|View full text |Cite
|
Sign up to set email alerts
|

Post–Coronavirus Disease 2019 Pulmonary Fibrosis: Wait or Needs Intervention

Abstract: Coronavirus disease 2019 (COVID-19) has become a major health burden worldwide, with over 450 million confirmed cases and 6 million deaths. Although the acute phase of COVID-19 management has been established, there is still a long way to go to evaluate the long-term clinical course or manage complications due to the relatively short outbreak of the virus. Pulmonary fibrosis is one of the most common respiratory complications associated with COVID-19. Scarring throughout the lungs after viral or bacterial pulm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 81 publications
0
8
0
Order By: Relevance
“…The complex and multifactorial nature of pulmonary brosis development in COVID-19 may also explain these inconsistencies. 23 A retrospective study conducted, 24 involving 227 patients with COVID-19, Li et al demonstrated a negative correlation between hemoglobin and pulmonary brosis (r = − 0.368, P < 0.001). In another study involving 159 patients, Zhang et al 25 reported that hemoglobin level can distinguish between patients with severe and non-severe COVID-19 infections, with an area under the curve of 0.79 in the receiver operating characteristic analysis, suggesting its utility in assessing disease severity.…”
Section: Discussionmentioning
confidence: 99%
“…The complex and multifactorial nature of pulmonary brosis development in COVID-19 may also explain these inconsistencies. 23 A retrospective study conducted, 24 involving 227 patients with COVID-19, Li et al demonstrated a negative correlation between hemoglobin and pulmonary brosis (r = − 0.368, P < 0.001). In another study involving 159 patients, Zhang et al 25 reported that hemoglobin level can distinguish between patients with severe and non-severe COVID-19 infections, with an area under the curve of 0.79 in the receiver operating characteristic analysis, suggesting its utility in assessing disease severity.…”
Section: Discussionmentioning
confidence: 99%
“…IPF and PCPF share similar clinicopathological features, such as reduced DLCO, disrupted alveolar‐capillary barriers, renin‐angiotensin‐aldosterone system imbalance, increased oxidative stress, and chronic inflammation. Hence, they both may respond to similar therapeutic strategies 5,15 . In the present study, we profiled single‐cell gene expression in the lung tissues of COVID‐19 and IPF patients.…”
Section: Introductionmentioning
confidence: 98%
“…Hence, they both may respond to similar therapeutic strategies. 5,15 In the present study, we profiled single-cell gene expression in the lung tissues of COVID-19 and IPF patients. Comparative single-cell transcriptome analyses revealed altered abundance and activity of individual cell types, prioritizing certain key cell types, cellular processes, signaling pathways, and genes may be common to both IPF and PCPF pathophysiology.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations